Les «verbes savonnettes»: frottements et glissements sémantiques - Surcouf, Christian (Neophilologica, 2014)
In the semantic analysis of tenses, the term event is frequently used. For example, following Reichenbach (1947: 288), many studies mention three “points”, within which (E) represents the “point of the event”. Besides, after Martin (1985: 25), it is commonly considered —often implicitly— that “the duration of the utterance can […] ideally be reduced to an instant t0 [i.e. a point], […] since within the utterance, truth conditions remain unchanged”. However, events as well as utterances take time (cf. the use of “intervals “ by Gosselin, 1996). Here, I will analyze present tense utterances such as “le ballon franchit la ligne” (the ball crosses / is crossing the line), for which the described event (“achievement” for Vendler, 1957; “instant realisation” for Vetters, 1996) is shorter than the utterance that mentions it. I will show why the telic character (Garey, 1957) of achievements — unlike the other types of processes — makes it difficult to express an event contemporary to speech time since, contra against Martin’s (1985: 25) idealization, truth conditions vary throughout the utterance. Taking encoding as the basis (somewhat following Levelt, 1989), I will argue that truthcondition variation can naturally lead to the over-represented use of past tenses (Passé composé in French) in child language for the expression of telic events during early acquisition (cf. e.g. Wagner, 2009).